Development of information supplement of reporting forms as an effective way of business management - Hevchuk, Anna; Shevchuk, Liudmyla (Technology audit and production reserves, 2021)
The object of research is the information support of settlement operations as an effective way of business management to minimize risks and their consequences in the agricultural sector in today’s global economy. This study is due to the lack of accounting practices, namely the low informativeness of reporting forms for business management, which needs to be improved in terms of settlement operations, which should be aimed at the efficient use of resources by agricultural companies. The analysis of the current state of reporting as information support of business management calculations is carried out. It is determined that the internal and financial reporting does not contain sufficient information on the settlement operations of business units, especially taking into account the emergence of new settlement instruments and a system of support for their implementation, including agricultural receipts. The use of agricultural receipts as a new financial calculation tool and an alternative mechanism for agribusiness lending requires informational reporting, which allows to increase the efficiency of management decisions. The study used the stages of modeling the calculation management process for users. For their implementation, the main directions for supplementing the content and components of financial statements f. No. 1 «Balance Sheet» (Statement of Financial Position) and f. No. 5 «Notes to the annual financial statements» are suggested. Management reporting is proposed, namely «Report on the status of settlements within accounts payable» and «Report on the status of settlements within accounts receivable». As well as the development of Section 4 «Risk Report» and Section 5 «Liquidity and Liabilities» of the Management Report. This provides an opportunity to generate useful, objective and relevant information adapted to the taxonomy of financial reporting (according to international financial reporting standards) in Ukraine. This information will assist company management, current and potential investors, lenders and other lenders in making effective management decisions. Compared to similar known methods, the proposed approaches allow to effectively manage the business, providing a high level of control over the state of settlements. The received information support will allow to minimize losses through the impact on risks due to the predictability of their potential consequences, which will contribute to the observance of financial independence and development of the agricultural sector.